The effect of bleaching on the optical and physical properties of externally stained monolithic zirconia - Maryam S. Tavangar; Elaheh Mousavipour; Elham Ansarifard (Wiley, 2021)
Abstract Objective This study aimed to investigate the effects of bleaching on the color, translucency, surface roughness, and surface hardness of monolithic zirconia with external stainin . Methods In this experimental study, 32 specimens of monolithic zirconia (1 × 1 mm; shade A2) were divided into two groups based on random permuted blocks. Overglaze and staining procedures were performed with a yellow stain or a value stain (GC Stain). Baseline color, translucency, roughness, and surface hardness were measured. The specimens were then randomly bleached with hydrogen peroxide (HP) 40% (20 min, twice with a 1‐week interval in between) as office bleaching or carbamide peroxide (CP) 20% (4 h per day for 14 days) as home bleaching. Finally, the color, translucency, surface roughness, and surface hardness were measured again. Results Bleaching with CP and HP caused a perceptible change in the color of the specimens (ΔE > 2), although this change was within the clinically acceptable range (ΔE < 3.3). HP significantly reduced the surface hardness of the specimens (p = 0.043). Changes in surface roughness of the specimens were neither statistically nor clinically significant (p = 0.19 and p = 0.25 for office and home bleaching, respectively). Conclusion The effects of home and office bleaching on the surface characteristics of monolithic zirconia were almost the same. It is not necessary to exchange or even to polish the surfaces of zirconia restorations after exposure to bleaching agents. Further studies are recommended to confirm the color stability of externally stained monolithic zirconia.